Analisis Perubahan Iklim terhadap Produktivitas Padi di Jawa Timur - Dicky Auliya; Akbar Hakim Rosandi; Waspodo Tjipto Subroto (Diponegoro Journal of Economics, 2024)
This study investigates the impact of climate factors on rice production in East Java, including variables such as rainfall, maximum temperature, and minimum annual temperature. The objective of this research is to determine how climate influences rice production in East Java. The study employs multiple regression analysis techniques, which allow for the estimation of long-term and short-term cointegration relationships among the analyzed variables. The results indicate that fluctuations in rainfall have a negative effect on rice production in East Java, while minimum and maximum temperature variables positively influence rice production in the region. The originality of this study lies in its provision of new insights into the effects of climate change on rice productivity in East Java, along with policy recommendations for climate change adaptation and mitigation.